DAMPAK PENGGUNAAN MEDIA BERBASIS ANDROID DALAM AKTIVITAS PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Ridwan Hermansah (Balai Diklat Keagamaan Bandung, 2022)
This study aims to determine the effect of using Android-based application on student activities in learning Islamic Cultural History. This classroom action research method is carried out in two cycles, where each cycle begins with planning, action, observation, and reflection. The data in this study are in form of assessments obtained in their activities and assessments at the end of the cycle. Then, the data is analyzed to obtain an overview of learning effectiveness that has been carried out. There are seven indicators that are measured to determine student activity in the learning process by applying the use of android-based media. The results showed that based on the seven indicators, there was an effect on increasing student learning activities in learning the subject of Islam spread in the archipelago by using an Android-based application. Before the action, only 37.62% students were actively involved in learning. In the first cycle, the average student learning activity increased to 56.19%. In the second cycle, the average student learning activity increased again reaching 76.16%. The conclusion is that the use of android-based media is very instrumental and suitable for increasing student activity in learning Islamic Cultural History at MTs Al-Ma'arif Cilageni, Garut.